Effects of oxidative stress and GDNF on patients with bipolar disorder: a prospective study - Qun Yang; Chuanwei Li; Fei Jiang; Jiancheng Qiu; Haidong Yang; Qing Tian; Xiaobin Zhang (BMC Psychiatry)
Abstract Background Bipolar disorder (BD) is a common mental disorder characterized by significant cognitive dysfunction, the mechanisms of which remain unclear. Oxidative stress and glial cell line-derived neurotrophic factor (GDNF) influence the pathophysiology of BD. Their specific roles, particularly concerning cognitive function during manic episodes, are unclear. The serum levels of superoxide dismutase (SOD) and malondialdehyde (MDA), and GDNF were biochemically assayed in patients with bipolar mania before and after treatment to explore their associations with cognitive function. Methods A total of 75 patients in acute manic episodes of BD and 70 healthy controls were initially enrolled. During the 4-week intervention period with atypical antipsychotics and mood stabilizers, 5 patients discontinued follow-up, resulting in 70 completers included in the final analysis. The severity of manic symptoms were assessed using the Young Mania Rating Scale (YMRS). Cognitive function was assessed by the Digit Cancellation, Stroop Color and Word, and Trail Making Tests. Serum levels of SOD, MDA, and GDNF were measured using biochemical assays. Results BD patients demonstrated higher serum SOD and MDA levels and lower GDNF levels compared to controls, following improvements after treatment. Pre-treatment YMRS scores and cognitive function assessments positively correlated with SOD and MDA levels, and negatively correlated with GDNF levels. Treatment significantly improved manic symptoms and cognitive function, although GDNF levels remained lower than in controls. Conclusions The demonstrated associations with symptoms and cognitive functions during the manic phase substantially advance the understanding of the role of oxidative stress and GDNF in BD. Possible biomarkers for BD diagnosis and prognosis assessment are revealed. Further investigations into the complex pathophysiological mechanisms of BD are needed. Clinical trial number Not applicable